The Influence of Work Motivation and Job Stress on Job Satisfaction of Entry Level Start-Up Employees - Nugroho, Ridho Bayu; Muljono, Pudji; Hidayatilloh, Furqon Syarief (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of work motivation and job stress on job satisfaction among entry-level employees in start-up companies. This phenomenon is particularly relevant given the dynamic nature of start-up work environments and the dominance of Generation Z in the workforce structure. Data were collected through questionnaires administered to 271 respondents working in the start-up sector and analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method. The results indicate that work motivation has a positive and significant effect on job satisfaction, while job stress has a significant negative effect. Simultaneously, both variables contribute significantly to job satisfaction, with an R² value of 0.925. These findings highlight that creating a work environment that fosters motivation while minimizing stress is essential to enhancing job satisfaction, particularly among Generation Z employees. This study provides theoretical implications for the development of human resource management research and practical recommendations for managing employees in competitive and adaptive start-up work environments.